Choques de precios externos y tipo de cambio real: La enfermedad holandesa ("dutch disease") en el caso argentino - Luis N. Lanteri (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2019)
– This paper analyzes the impact of external price shocks on the real exchange rate and the existence of the Dutch disease, in the case of the Argentine economy. We consider the effects of shocks on the terms of trade, the supply of the agricultural sector (booming sector) and the real exchange rate on the GDP of the manufacturing sector (or, alternatively, on total GDP) and unemployment rates. SVAR models, with long-term restrictions, and quarterly data, covering the 1993-2018 period, are estimated. The results show that the external price shocks and agricultural sector shocks affect positively and permanently to the manufacturing GDP and negatively to the unemployment rates, not finding substantial evidence about existence of the Dutch disease for this economy.
Keywords: C32; F41; 330; external price shocks; real exchange rate; Dutch disease; SVAR models; Argentina